The Effect of Parenting Styles Based on Teeneger Approaches to Prevention of Free Association in Teeneger in Padangsidimpuan - Mustika Pane; Mutia Sari Lubis; Rini Amalia Batubara (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2024)
Introduction: Free association is a form of association that isn’t bound by social rules and norms caused by a person's inability to sort out information that must be applied in everyday life. Promiscuity is synonymous with teenagers Objective: This research aims to analyze the influence of parenting styles based on adolescent approaches to preventing promiscuity Method: This research is quantitative type with the method used retrospective research, because the researcher will explore teenagers' experiences related to parenting patterns carried out by parents in everyday life, and without any treatment. The sample size was 120 respondents. Result: The results found that the majority of respondents had an authoritative parenting style, 107 people (89.2%). Based on preventing promiscuity, the majority were able to prevent 112 people (93.3%). The bivariate results for both variables show that the p-value is 0.011, which can be interpreted as having an influence on parental parenting on preventing juvenile delinquency (0.011 < 0.05) Conclusion: Actions to prevent promiscuity according to teenagers are closely related to the parenting patterns used by parents. Authoritative parenting is the best parenting style compared to other parenting styles in caring for teenagers. This is because this parenting style provides teaching in the form of a sense of responsibility and explanation in every action, so that teenagers will understand the reasons for what actions they can and cannot take.